Mediating roles of consumer individual values on the relationship between exposure to global marketing activities and consumption behavior - Akhoundi, Maryam; Osman, Syuhaily; Paim, Laily; Nezakati, Hossein (Malaysian Consumer and Family Economics Association, 2017)
The main goal of this study to investigate the mediating effects of consumer individual values on the relationship between exposure to global marketing activities and consumption behavior. To this end, at first the study tests the previous proposition of direct path of the effect of exposure to global marketing activities on consumption behavior (of global foods and drinks, global clothing and accessories, household appliances and communications), then to examine the mediating effects of consumer individual values on fundemental relationships using Schwartz's basic values. This research supported the significant contribution of predictor variable to consumption behavior of four proposed product categories, among them the mediating roles of consumer individual values were observed on consumption behavior of household appliances and communications. The study also highlighted significant implications for consumer affairs specialists and managers.